Diversity of arbuscular mycorrhizal fungi in the rhizosphere of saffron (Crocus sativus) plants along with age of plantation in Taliouine region in Morocco - Ourras, Samah; EL Gabardi, Soumaya; El Aymani, Ismail; Mouden, Najoua; Chliyeh, Mohamed; Selmaoui, Karima; Msairi, Soukaina; Benkirane, Rachid; El Modafar, Cherkaoui; Ouazzani Touhami, Amina; Douira, Allal (Acta Biologica Szegediensis, 2022)
Saffron cultivation is a viable alternative for marginal areas where low soil fertility and water availability severely limit the cultivation of other crops with higher water and input requirments. Under these conditions, arbuscular mycorrhizal fungi (AMF) are an essential alternative for maintaining fertility and water conservation, stimulating growth, and providing plant protection against soil-borne diseases. The aim of this work is to highlight the diversity of the arbuscular mycorrhizal fungi communities associated with saffron roots in plantations of different ages (two, four and ten years old) in the region of Taliouine (Morocco). The highest number of endomycorrhizal spores was recorded in the rhizosphere of saffron plants harvested at the level of plots that have carried saffron for two years (138.66/100 g soil), while the lowest number was observed in the rhizosphere of plants of plots that are occupied for 10 years by saffron. All collected spores from plots under study represent 17 morphotypes belonging to 5 genera: Glomus (7 species), Acaulospora (7 species), Rhizophagus (one species), Densicitata (one species), and Funneliformis (one species).